Distúrbios do sono em discentes de graduação do ISB/UFAM, no município de Coari – Am - Severino, Letícia Seixas (Brasil, 2024)
Sleep plays a crucial role in maintaining health, allowing the body to rest and recover. During sleep, revitalization and recovery processes occur to compensate for energy expenditure during the day. However, sleep disorders can arise, affecting both physical and mental health. One of these disorders is insomnia, characterized by difficulties in initiating or maintaining sleep, resulting in unsatisfactory sleep and nocturnal awakenings. College students are particularly susceptible to mental disorders sleep, due to academic pressures and changes in routine. Previous research shows that many of them compromise their sleep hours to meet academic deadlines, leading to loss of enthusiasm for everyday activities. Some studies indicate that sleep disorders significantly affect the quality of life of university students, with rates alarming reports of poor sleep quality and the use of over-the-counter sleeping pills. This study aims to analyze the prevalence of sleep disorders in high school students. degree from the Institute of Health and Biotechnology (ISB) at the Federal University of Amazonas (UFAM) located in Coari, Amazonas. The research is cross-sectional and quantitative in nature, carried out between 2022 and 2023. The study sample included 149 students from various courses degree from ISB/UFAM. Data were collected through an electronic questionnaire, including socioeconomic and demographic information, as well as the Quality of Pittsburgh Sleep Index (PSQI) to assess sleep quality and possible disorders. The results Initial reports show a variety of sleep patterns among students, with a percentage significant rating your sleep quality as "poor". Furthermore, data analysis reveals associations between sleep quality and factors such as age group, family income and course of graduation. This study seeks to fill a gap in research on sleep disorders in university students, specifically in remote geographic regions, such as the interior of Amazon. The results are expected to contribute to the development of strategies for improve the quality of sleep and academic performance of these students.